Ghaznavid dynasty - Tursunaliyev, Azizbek (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
The article examines the formation of the Ghaznavid dynasty, its political development, and its role in the history of the region. The study analyzes the military power, economic life, and cultural traditions of the state during the reigns of Sabuktegin and Sultan Mahmud of Ghazni. The article also provides information about the Ghaznavids’ campaigns in India and the political consequences of these expeditions. Furthermore, it covers the factors that led to the decline of the Ghaznavid state and the processes associated with its dissolution by the Ghurids. The findings demonstrate that the Ghaznavid state held an important place in the history of the medieval Islamic East.